Studi Perencanaan Sistem Jaringan Pipa Distribusi Air Bersih dengan Software WaterCAD di Perumahan Green Orchid Residence Kota Malang - Rusardi, Olda Fadhilah Aprilia; Prayogo, Tri Budi; Dermawan, Very (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
Green Orchid Residence planned 968 houses with considering the futureidevelopment. This studyiaimed to determineithe existing conditions and development conditions at the study site based on the existing hydrauliciconditions. Simulation of water distributioniinetwork are usingiWaterCAD V8iisoftware application. Totalidischarge on the distribution pipe is 527,5 l/s and the available discharge is 72,5 l/s. According to the calculation of total dischargeirequired at the planning and development phase, the average dischargeirequired is 27,1 l/s. The calculation is based on the water needs fluctuation with the discharge changing according to the load factor of each hours. There are two alternative plans, first is according to existing conditions (all pumps are on) and second with changing of working hours of the pump and addition a new pump with centrifugal type. Also there are two alternative for future development, alternative 3 with addition 532 houses and alternative 4 with addition 500 houses. The simulation result showing the hydraulic condition, which 0,1 – 2,5 m/s of velocity, 0,5 – 15,0 m/km of headloss gradient and 0,5 – 8,0 atm of pressure. The cost estimation for the first alternative is Rp 688.494.800,00, the second alternative is Rp 729.885.600,00, the third alternative is Rp 823.588.200,00 and the fourth alternative is Rp 974.403.900,00. Keywords: WaterCAD, water, pipe network, planning, cost estimation